Phenol Removal from Aqueous Solution by Adsorption Technique Using Coconut Shell Activated Carbon - Zhi Hoong Ho; Liyana Amalina Adnan (Tropical Aquatic and Soil Pollution, 2021)
Adsorption is one of the simplest techniques with low economic requirements. Coconut shell is an abundant agriculture waste which is inexpensive and easy to be obtained in Malaysia. This agriculture waste was transformed to activated carbon via 600°C of carbonization and zinc chloride activation. The ability of coconut shell-based activated carbon to remove phenolic compounds from aqueous solutions was evaluated. From the experiment, the equilibrium time for the adsorption of phenol onto coconut shell-based activated carbon is 120 minutes. The effect of the operating parameters, such as contact time, initial concentration, agitation speed, adsorbent dosage, and pH of the phenolic solution were studied. Adsorption kinetics models (pseudo-first-order, pseudo-second-order, and Elovich equation) and isotherm models (Langmuir, Freundlich, Temkin, and Dubinin-Radushkevich) were used to fit the experimental data.Pseudo-second-order was found to be the best fitted kinetics model to describe the adsorption of phenol on coconut shell-based activated carbon. While the equilibrium experiment data was well expressed by the Temkin isotherm model, The maximum adsorption capacity is determined as 19.02 mg/g, which is comparatively lower than the previous research. Meanwhile, 92% of removal efficiency was achieved by a dosage of 10g/L. Meanwhile, the adsorption of phenol by activated carbon was more favorable under acidic conditions. The favourable isotherm behavior was indicated by the dimensionless separation factor. The functional group and compound class of activated carbon before and after the experiment were determined through the analysis of Fourier-transform infrared (FTIR) spectroscopy.